2009
DOI: 10.1111/j.1467-8551.2008.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Getting Together to Get Ahead: The Impact of Social Structure on Women's Networking

Abstract: This paper examines the impact of socio-structural variables (i.e. perceptions of permeability, stability and legitimacy of intergroup relations) on the extent to which professional women perceive a women's network as a collective strategy for status enhancement. A survey among network members (n 5 166) suggests that the extent to which women support and consider a network to benefit women as a collective is dependent on perceptions of whether individual mobility is possible (permeability of group boundaries) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 46 publications
2
62
0
3
Order By: Relevance
“…The null effects of legitimacy and stability are surprising given that previous work has found that legitimacy Hersby et al, 2011) and stability (Hersby et al, 2009) influence women's engagement in collective enhancement strategies. These unexpected null effects may have been at least partially due to our methodology.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 68%
See 4 more Smart Citations
“…The null effects of legitimacy and stability are surprising given that previous work has found that legitimacy Hersby et al, 2011) and stability (Hersby et al, 2009) influence women's engagement in collective enhancement strategies. These unexpected null effects may have been at least partially due to our methodology.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 68%
“…Though finding no impact of legitimacy appraisals, Hersby, Ryan, and Jetten (2009) found an interactive effect of status stability and permeability on women's support for a women's network initiative. Women supported the initiative more when they evaluated group status relations in the organisation as being unstable and permeable (versus stable and permeable) suggesting that when group advancement is possible individual mobility attempts are negated.…”
Section: The Impact Of Sociostructural Variablesmentioning
confidence: 91%
See 3 more Smart Citations